Fiscal fault, financial fix? Capital markets union and the quest for macroeconomic stabilization in the euro area - Braun, Benjamin; Hübner, Marina (Köln, 2017)
"This paper argues that Capital Markets Union – the EU's attempt to establish a more market-based financial system – is a result less of financial policymaking than of macroeconomic governance in a politically fractured polity. The current governance structure of Economic and Monetary Union (EMU) severely limits the capacity of both national and supranational actors to provide a core public good, macroeconomic stabilization. While member states have institutionalized fiscal austerity and abandoned other macroeconomic levers, the European polity lacks the fiscal resources necessary to achieve stable macroeconomic conditions: smoothing the business cycle, ensuring growth and job creation, and mitigating the impact of asymmetric output shocks on consumption. Capital Markets Union, we argue, is an attempt by European policymakers to devise a financial fix for this structural capacity gap. Using its regulatory powers, the European Commission, supported by the European Central Bank (ECB), seeks to harness private financial markets and instruments to provide the public policy good of macroeconomic stabilization. We trace how technocrats, think tanks, and financial-sector lobbyists, through the strategic use of knowledge and expertise, established securitization and market-based finance as solutions to EMU's governance problems. "